Incidence of Entamoebiasis Among Children In Abu -Ghraib Area Baghdad - Al -Azawi, Athmar k. Abass (The Iraqi Journal of Veterinary Medicine, 2009)
A total number of 600 fecal samples were collected from patients attaining general Abu-Ghraib hospital during the period from 1st march 2006 till 28th February 2007. The samples wereexamined for detection of intestinal protozoan Entamoeba(E).histolytica infection by direct smear withIodine stain and flotation technic using Zinc sulphat solution .The overall rate of infection was32.5%.Asignificant differences were observed in the rates of infection between males and femaleswhich constituted 46.44%, 25.64% respectively. All age groups were infected, the highest rate ofinfection 61.9%, 29.6% were noticed in males and females of 2-5 years old respectively, whereas thelowest rates 15.15%, 10% were recorded at the age of 9-11 years respectively . The incidence of E.histolytica infection was observed allover the year, and the highest rates of infection 51.3%, 38%wererecorded in spring and summer respectively .while the lowest rate 18.6% was noticed in full.Meanwhile it was 14% in winter season